التحليل المكاني لأخطار السيول وتأثيرها على التنمية المتواصلة بمنطقة رأس غارب على الساحل الغربي لخليج السويس "مصر" - أبو راضي، فتحي عبدالعزيز Abu Radi, Fathi Abdulaziz; عجوة، وليد محمد علي محمود (الجمعية الجغرافية المصرية, 2019)
تهدف هذه الورقة البحثية إلى معرفة مدى تأثر التنمية بمنطقة رأس غارب بأخطار السيول في إطار منهجية التحليل المكانيSpatial Analysis ، وذلك لأهميتها في رسم الخطط التنموية، واتخاذ المختصين القرارات الخاصة بشأن التنمية. وقد تناولت الدراسة الحالية التحديد الدقيق لموقع منطقة البحث، ودراسة الخصائص الطبيعية، وتأثيرها في تحديد مدى خطورة السيول على التنمية المستدامة في المنطقة. كما اهتم البحث بدراسة التحليل المورفومترى لأحواض وشبكات التصريف السطحي في منطقة الدراسة، وذلك لأهميتها في التعرف على حجم التصريف المائي. هذا بالإضافة إلى دراسة الخصائص التضاريسية لأحواض التصريف، وخصائص شبكات التصريف الرئيسة للتعرف على التأثير المتبادل بين العمليات الجيومورفولوجية - خاصة عمليات التعرية المائية - وأحواض تصريف الأودية الجافة. واهتم البحث أيضا بدراسة المؤثرات الهيدروجيومورفولوجية للجريان السيلي، من حيت زمن التركيز والذي يشير إلى سرعة وصول المياه إلى النطاقات العمرانية، والطرق. كما يوضح الآثار التدميرية للسيول على العمران والزراعات والطرق. كما تناول البحث دراسة تقدير درجة احتمالية حدوث السيول عن طريق دراسة المتغيرات الهيدروجيومورفولوجية للجريان السيلي بأحواض التصريف، بالإضافة إلى دراسة الأخطار الناجمة عن السيول، وذلك من خلال دراسة خصائص الكتلة العمرانية المتأثرة بالسيول، وتأثير السيول على شبكة الطرق بمنطقة الدراسة.
This study aimed to show spatial analysis for the flash floods hazards of its impact on sustainable development at the area of Ras Ghareb which located on the western coast of Suiz Gulf. The research shows the area's natural characteristics. The study of that characteristics clears that the area consider one of the most threaten areas with flash floods because of its natural characteristics. The study of area's Topography characteristics with digital height analysis and gradient map and Topographic sections verified that characteristics as mentioned made the area would be one of the most affected by flash floods hazards. The north of it like Abo Had Valley. Gradient analysis shows how suitable this area for flash floods movements towards buildings and roads as what had happened in Ras Ghareb city before in 2016. The research cares to study morphometric characteristics for basins and uncovered drainage grids which affect the study area. Through study of the area's characteristics of drainage basins which prove basins verification in areas, width, length and circumference of each one. All above mentioned prove that the area is one of the most affected areas which flash floods threaten it with hazards on sustainable development in Egypt. The study of formalisms drainage basins (Elongation Ratio, Circularity Ratio, Form Shape Factor) shows most of those basins are low in elongation ratio which lead to progress in its cycle and dominion vertical sculpture operations in its streams. The study of topographic characteristics for drainage basins point that the basins which increase in Relief Ratio increase in sudden floods summit. Those made the area threaten by flash floods hazards. The research also cares about the study of drainage grids (stream class, number, ratio, length, Aggregation Ratio … etc.) which shows most of them are from the first and the second class streams. Also the first class streams increase in number of basins. Abo Had Valley and Dob Valley record the most large number in the first class streams. Aggregation ratio points to verification in aggregation ratio of study basins area and the basin of Dob Valley and Korm El Ghoyreb are the most affected by flash floods hazards. The drainage density of the area is 0.11 in Ghareb Valley basin and 1.83 in Koriem Valley basin. That because of the small area and the short drainage grids which made it one of the most hazards basins related to flash floods. And it has been possible from studying the main drainage that affecting on inhabited areas and the roads, studying Hydro-geomorphology impacts for flash floods running streams pinpoint the rang of hazards for flash floods in the area. It shows that time aggregation ratio decreases in general and water speed ratio increases in the area. That point to the highly degree in hazard from flash floods. Finally the recent study determines the most suitable ways to protect us from flash floods hazards at the research area.
Keywords: الجغرافيا الطبيعية -- السيول -- التنمية -- منطقة رأس غارب -- مصر